2004
DOI: 10.1038/emm.2004.76
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of Korean type hepatitis C virus core protein and related mutants in mice

Abstract: A bstract H epatitis C virus (H CV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The results showed that NS4B was expressed widely in the tissues of transgenic mice, including the liver, but was not expressed in normal control littermates ( Figure 1B and C). This expression pattern was similar to the pattern that appeared in the transgenic mice expressing the HBV X protein and HCV core protein under the direction of the HBV enhancer sequence in our previous study (Yu et al, 1999;Wang et al, 2004). To find out if the mRNA was translated to the protein in the liver, Western blot analysis and immunohistostaining were performed.…”
Section: Expression Of the Ns4b Transgenesupporting
confidence: 79%
See 2 more Smart Citations
“…The results showed that NS4B was expressed widely in the tissues of transgenic mice, including the liver, but was not expressed in normal control littermates ( Figure 1B and C). This expression pattern was similar to the pattern that appeared in the transgenic mice expressing the HBV X protein and HCV core protein under the direction of the HBV enhancer sequence in our previous study (Yu et al, 1999;Wang et al, 2004). To find out if the mRNA was translated to the protein in the liver, Western blot analysis and immunohistostaining were performed.…”
Section: Expression Of the Ns4b Transgenesupporting
confidence: 79%
“…However, the expression of NS4B was not cytopathic to liver tissue and to other cell types in these mice. Compared with the tumorigenesis and cell dysplasia in liver tissues of our previously reported HBX and S99Q transgenic mice, which were produced using the same HBV enhancer to induce the expression of transgenes (Yu et al, 1999;Wang et al, 2004), the non-pathologic changes detected in our NS4B transgenic lineages indicated a non-cytopathic function of NS4B in most cell types, even though the in vitro investigation showed the possibility of functions relating to the cell cycle (Florese et al, 2002) or transformation (Park et al, 2000, Qu et al, 2001). An understanding of HCV-mediated pathogenesis and the control of HCV infection have been impaired in part because of the unavailability of an efficient cell culture system for virus growth and a convenient small animal model.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The transgenic mice used in this study were generated as previously described [19]. They were produced by the injection of the HCV core gene and its mutant genes under a transcriptional regulatory element from HBV enhancer into mouse embryos obtained from F1 hybrid of C57BL/6 and CBA.…”
Section: Methodsmentioning
confidence: 99%
“…Recently three transgenic mouse lines were created expressing the HCV core gene and its mutants in liver [19]. One is the transgenic mice model, which has a wild type core (TG-K).…”
Section: Introductionmentioning
confidence: 99%